The Influence of Reward Systems, Decentralization and Implementation of TQM on Managerial Performance of Schools Leaders - Glisina Dwinoor Rembulan; Egi Rodlia Fitri; Tanti Widia Nurdiani; Sudadi Sudadi; Ratih Kusumastuti (Departement of Mathematics Education, 2023)
This study seeks to determine the impact of implementing good management as a whole, overall performance measurement structure, reward system, and decentralization on managerial performance in several private schools in Jakarta and Tangerang. Likert scale is used to collect important facts for this study. As the study sample, five schools have been selected. The method used in this research technique is a quantitative method. This study involved 60 respondents. Validity testing was carried out with Pearson correlation, reliability testing with Cronbach's alpha, and hypothesis testing with multiple regression analysis techniques. The consequence of this observation reveals that management performance is generally good, with an importance value of 0.000, some of which have effects that can be applied to managerial performance. These results are based on statistical tests with a significance level of 5%. Good management as a whole, overall performance measurement tools, reward tools, and decentralization all have a significant effect on managerial performance with a significance cost of 0.00, while performance dimension tools, reward machines, and decentralization have no significance value with values of 0.055, 0.500, and 0.071.